INTERFACE DESIGN FOR A DBMS - Syed Abd. Rahman, Syarifah Nasyua (Universiti Teknologi Petronas, 2004)
This research serves as the initial delivery and as a guideline for the project, which contains an overview of the project background of study, problems that have been identified, and how do the author see the project's usefulness for users of a DBMS. The main objectives of this study is to do research on the usage and effect of Human Computer Interaction (HCI) and the effect of applying it in the User Interface (UI) Design, to review the current DBMS interface andcompare it withthe proper elements of the UI Design, to produce a new guidelines regarding this area of research and also to produce with the refined prototype of theDBMS interface. For this purpose, the author has chosen the TOAD software, which is a DBMS tool to be compared and analyzed according to the elements and guidelines of HCI. Poor representation of the graphical user interface will lead to confusion and misinterpretation by the users and to overcome the matter, the author will come out with a proper set of guidelines as well as a refined set of interface which is more user-friendly and efficient. In orderto accomplish this project, the author has followed the methodology, which begins with the Research/Analysis phase, Conceptual Design phase, Physical Design and ends with User Testing phases. Based on the result and findings, the main factor that contributes to the ineffectiveness of a user interface is the lack of consideration and planning on the design of the user interface as most of the programmers focus on the coding part of the design. This will lead to improper usage of terms and inappropriate metaphors. In conclusion, the importance of the usage and consideration of using HCI in designing the user interface is applicable not only for this project, but to any software developers in developing a useful and efficient programs.